PTU-257 Correlation of adipokines and intestinal inflammation with mesenteric adipose tissue volumes in symptomatic and asymptomatic diverticulosis. (22nd June 2015) - Murray, K; Hoad, C; Garratt, J; Costigan, C; Batra, A; Siegmund, B; Falcone, Y; Cox, E; Paul, J; Smith, J; Humes, D; Francis, S; et al.
Abstract : Introduction: Colonic diverticulosis affects up to 66% of those > 65 years in the UK. Obesity is a risk factor for developing symptomatic diverticular disease (DD) including abscess formation and perforation. These inflammatory complications may relate to the known pro-inflammatory secretions (adipokines and cytokines) of visceral adipose tissue (VAT). This study looks at correlations between abdominal adipose tissue and adipokines and symptoms in DD by comparing asymptomatic (ASYMP) and symptomatic patients (SYMPDD). Method: 55 patients, BMI 20.5–39.5 kg m -2 comprising 17 ASYMP and 38 SYMPDD with chronic abdominal pain (29 with somatization score (PHQ12-SS) ≥7 and 9 <7). All were scanned with a 1.5T MRI scanner after an overnight fast. Blood and stool samples were collected and concentrations of adiponectin, leptin and faecal calprotectin were determined. Results: SYMPDD patients had more fat, leptin and calprotectin than ASYMP but these differences were not significant (Table 1 ). However overall (n = 55) adiponectin was found to correlate negatively with VAT (r = -0.344, p = 0.01), abdominal volume (r = -0.510, p = 0.0002), and BMI (r = -0.425, p = 0.002). Leptin in contrast correlated strongly with SAT (r = 0.762, p < 0.0001) and TAT (r = 0.698, p < 0.0001), while the correlation with VAT was weaker (r = 0.384, p = 0.004). Stool calprotectin correlated negatively with adiponectin (r = -0.353, p = 0.009) and weakly with stool frequency in SYMPDD patients but this was not significant (Spearman r = 0.3, P = 0.057). Stool form correlated positively with BMI (Spearman r = 0.4, P = 0.005). SS were significantly higher in SYMPDD versus ASYMP patients (P < 0.001). Conclusion: MR imaging demonstrates that VAT, SAT and TAT correlated with both adipokine concentrations and faecal calprotectin in DD patients. The study confirms the known link between leptin, adiponectin and obesity, and shows that abdominal VAT is related to intestinal inflammation. Whether this link is primary or secondary due to differences in diet or microbiota or both remains to be established. Disclosure of interest: None Declared.